Improving Student Activity And Learning Outcomes in English Course in Writing News Item Text through Discovery Learning Model in Class XII IPA 1 SMAN 12 Banjarmasin - Ronny Ralin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Lack of students in learning to write is the lack of activity and motivation of students so that learning to write becomes a problem. The application of the discovery learning model is very appropriate to solve this problem. Learning with discovery learning model with news item text material in the first cycle there were 18 students (72%) who completed the increase in the second cycle to 23 students (92%).